Characteristics of learning and training of elite athletics in Brazil: the perspective of experienced coaches - Caregnato, André Felipe (2020)
The present study sought to verify the perspective of the coaches regarding the teaching, learning and training process in Brazilian Athletics. Semi-structured interviews were applied to six Brazilian athletics coaches with participation in the Olympic Games. From the interviews, two categories were defined: formation and development of athletes; talent and long-term training. About the age indicated to start in athletics, the coaches reported that the ideal (f = 56.90%) is that the athlete starts in the sport in the youth. However, they chose not to stipulate a single age group to start in the sport. Characteristics that induce the organization of a work model in athletics (f= 26.14%) were frequent in the speeches. There was a lack of specific parameters on how the profession of coaching should be exercised - in this case athletics - it is necessary to have structures that enable the development of the coach’s career.